Tunability of form birefringence induced by femtosecond laser irradiation in anion‐doped silica glass. Issue 9 (22nd May 2017) - Shimotsuma, Yasuhiko; Kubota, Sho; Murata, Atsushi; Kurita, Torataro; Sakakura, Masaaki; Miura, Kiyotka; Lancry, Matthieu; Poumellec, Bertrand
Abstract: Form birefringence originating from self‐assembly of the bulk nanograting structures in silica glass with various anion dopants (OH, Cl and F) was induced by the femtosecond laser pulses. Despite the almost similar nanostructure, the photo‐induced birefringence can be changed by the anion dopants in glass. Larger birefringence can be induced in silica glass doped with higher Cl ion concentration. Even if F‐doped silica glass indicates lower thermal stability, its lifetime could be evaluated to be at least several billion years.